The impact of the empowerment strategy in the employees performance by mediating organizational trust (Field res - الكبيسي صلاح الدين عواد; عذيب رعد فرحان (Journal of Economics and Administrative Sciences, 2020)
The research aims to measure the impact of the empowerment strategy on the performance of employees by mediating organizational trust in the organization. The problem of research was the weak ability of most business organizations to employ the strategy of empowerment in maximizing the performance of employees, and the importance of research in practice lies in the results of a guide to managers in how to use the strategy of empowerment in maximizing the performance of employees by mediating organizational trust dimensions of ability, benevolence, integrity. In order to achieve the objectives of the research and to answer the questions of the problem, the researcher has adopted the descriptive analytical approach as the questionnaire was used to collect data from the research community represented by the category of engineers (266) engineers in the oil pipelines company. According to the Ministry of Oil, the size of the sample drawn from this category was (159) engineers, in addition to personal interviews and field visits to the researcher that had the same purpose. Data were analyzed and processed statistically using the program (spss.v 24), which included a set of statistical methods, such as arithmetic mean, iterations, percentages, standard deviation, coefficient of variation, the coefficient of stability Gutman and Alfa Cronbach, test (F), exploratory factor analysis, and mid-segmentation. The results of the researcher, there is a positive correlation between the positive impact between the strategy of empowerment, organizational trust, between the strategy of empowerment and employee performance as well as the relationship and impact of organizational trust with and in the performance of employees. The impact of the strategy of empowerment on the performance of employees is increased through organizational trust, which confirms the intermediary role.